2020
DOI: 10.1039/c9qm00772e
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic frameworks as a compatible reinforcement in a biopolymer bone scaffold

Abstract: The insufficient mechanical strength and slow degradation rate of poly-l-lactic acid (PLLA) limit its applications in bone repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 54 publications
0
47
0
1
Order By: Relevance
“…Using stem cell self‐renewal and differentiation ability to treat osteoporosis may be the most potential way of bone repair, which is expected to solve the medical problems of bone regeneration and repair 29 . In recent years, biological scaffolds have made rapid progress 30‐33 . It is particularly urgent to clarify the mechanism of stem cell differentiation and develop new strategies to induce stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Using stem cell self‐renewal and differentiation ability to treat osteoporosis may be the most potential way of bone repair, which is expected to solve the medical problems of bone regeneration and repair 29 . In recent years, biological scaffolds have made rapid progress 30‐33 . It is particularly urgent to clarify the mechanism of stem cell differentiation and develop new strategies to induce stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous studies ( 2 , 30 32 ), combining bioactive molecules, such as growth factors, peptides and small molecules with corresponding bone scaffold may lead to effective clinical transformation and provide new insights into the future of bone transplantation. Notably, this study demonstrated that NPY signaling directly promotes osteogenic differentiation of MC3T3-E1 cells by upregulating Runx2 and osterix in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques such as salt leaching 6 , fibrous fabric processing 7 , woven fabric processing 8 , gas forming 9 , emulsion freeze-drying 10 , electro spinning 11 , three dimensional printing 12 , and phase separation 13 have been developed to fabricate porous biodegradable polymer scaffolds. In addition, various techniques for the fabrication of biodegradable polymeric scaffolds have been tried recently to increase the strength and the antibacterial activity of scaffolds 14 16 .…”
Section: Introductionmentioning
confidence: 99%